An Exploration into Student and Teacher Perceptions on the Use of Authentic Materials in an English for Medical Science Programme at a South Korean University - Pettifer, Guy (2016)
Four years ago, Sungshin Women’s University selected some English language teachers to increase the English ability of third and fourth year medical science students. Although it is considered a general English programme for the students, over the years there has been an attempt by the teachers on the programme to introduce more medical specific materials, largely through scrapping general English textbooks and finding authentic materials. The idea is that the use of authentic materials can help students learn realistic language (Benavent and Penamaria, 2011), increase their motivation (Crookes and Schmidt, 1991, cited in Peacock, 1997), and introduce them to the cultures of other counties they may have intentions of working in, in the future (Berardo, 2006; Garcia, 1991). However, the use of authentic materials must be used with some caution. Common authentic materials such as TV dramas and newspaper articles often contain language that is complex (Ciornei and Dina, 2014), is demotivating (Richards, 2001) and can show the wrong impression of other cultures (Kilickaya, 2004; Martinez, 2002). Although, selecting authentic material can be burdensome for teachers, it is important that they find authentic material and produce associated tasks that are appropriate for the students (Darwish, 2014). The aim of this study was to assess, by use of questionnaires and interviews on students and teachers, the effectiveness of authentic materials within the English for Medical Science Programme at Sungshin Women’s University. After the data was gathered, the results were then triangulated between lower levels students, higher level students and teachers. The findings suggest that the authentic materials used in the programme were beneficial. Particularly the use of medical related articles and TV dramas, documentaries and movies were helpful for the students to learn realistic and relevant language. At the same time, they were considered to be motivating and helpful to learn about culture within medicine in other countries. Nevertheless, the findings also revealed a concern over the difficulty of the language in authentic materials and consequent frustration, especially when students had to watch TV dramas, documentaries and movies. More so, it also became apparent that some authentic materials, particularly newspaper articles, TV dramas and movies may often show an overtly negative focus on western culture such as crime and violence. Although there was a divide of opinion over the difficulty of preparing authentic materials, it became evident, that authentic materials must be appropriate for the learner. As was revealed, finding appropriate authentic material that may be edited to an extent, with suitable educational and pragmatic tasks for the Medical Science students are important considerations. The findings of this study, imply that students can greatly benefit from continued use of subject related authentic material. They should be carefully selected by the teacher and considered by the institution to be an integral part of making the programme into a formalised Medical Science English programme.